Controlled Release of Propionic Acid and (E)‐2‐Hexenal Against Sitophilus Granarius (L.) (Coleoptera: Curculionidae). Issue 2 (27th January 2014) - Germinara, G.S.; Conte, A.; Lecce, L.; Di Palma, A.; Contò, F.; Del Nobile, M.A.
Abstract The purpose of this study was to develop biodegradable devices for controlled delivery of natural fumigants. To this aim, a porous core based on whey protein foam was first loaded with either propionic acid or (E)‐2‐hexenal and then coated with a multilayer of poly‐caprolactone to delay compounds release. The release mechanism of compounds from the matrix system has been explored and described by means of a mathematical model. It was found that the experimental data are satisfactory analyzed using a diffusion‐controlled model, thus calculating all the parameters that control the release. Fumigants' toxicity highlighted that both compounds investigated in this study are proven candidates to be formulated in sustained release dosage form and have been subjected to thorough investigation for their candidature. Practical Applications Devices assuring a controlled release of propionic acid and (E)‐2‐hexenal can find practical application for the control of insect pests in stored cereal grains. Biodegradable formulations of natural fumigants are particularly interesting for the storage of cereals from organic farming.